Finite Volume Simulation Of Flow Of Polymer In An Extrusion Die - Yasir, Widad Shahira (Universiti Sains Malaysia, 2017)
Rheology is the behavior of flow of polymer. The aim of the study was to observed and understands the behavior of the flow of Low Density Polyethylene (LDPE) through an extrusion die. Three dimensional (3D) simulation of polymer rheology in an single screw extrusion was used. In this simulation, the FLUENT 15.0 software was used to verify the viscosity model (Cross model). This study was determined the effect of process parameter on die swell behavior. Simulation was carried out on the different temperature and pressure. The higher the temperature result in decreasing the die swell ratio. The effect of pressure shows increasing the pressure will increase the die swell ratio. There was some effect on the die swell that influenced by molecular weight of the polymer. This was observed by comparing Low Density Polyethylene with Polylactic Acid (PLA). LDPE shows to have lower die swell ratio. The affect in process parameters such as temperature, screw speed and pressure on its rheology were studied. The process parameters such as temperature and pressure were found to have prominent influences on the viscosity of the LDPE melt. Besides that, the flow pattern was observed that polymer melt become straightens towards the extrusion die. The study in simulation of flow of polymer had to consider various parameters. The strength of FLUENT 15.0 in handling simulation of extrusion process needed to study more detail to get excellent and better results.